Echocardiographic Differential Diagnosis of the Cyanotic Newborn - Deeg, K. H. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Cyanosis in newborns can be caused by cyanotic heart defects, such as transposition of the great arteries, tetralogy of Fallot, pulmonary and tricuspid atresia, hypoplastic left heart syndrome, common arterial trunk, Ebstein's anomaly of the tricuspid valve, and total anomalous pulmonary venous return. The indicated cyanotic heart defects can be diagnosed or ruled out with three simple echocardiographic views: The parasternal long and short axis view and the apical or subcostal 4-chamber view. If these three views are normal, a cyanotic heart defect can be ruled out. In the case of a cyanotic heart defect, one or more views are pathological.